Pengaruh Persepsi Pegawai Akan Program Germas Terhadap Perilaku Hidup Sehat di Lingkungan Kerja Badan Narkotika Nasional - Indradewi, Regina Nova; Purwaningsih, Wahyu; Samputra, Palupi Lindiasari (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 2 Tahun 2019, 2019)
Abstract The purposes of the research are to analyzing, evaluating, and measuring the correlation between employee's perception of Germas (healthy life movement) on the behaviour of healthy living in the work environment, according to the recommendations in Germas as a policy of the Natonal Narcotics Board (NNB). Data is analysed by factor analyze and multiple regression method. Ordinal data obtained from filling out the quetionnaire must be chenge first to interval data using Method of Succesive Interval.  Data is processed by using SPSS 23. The results shows that with a significance level of 5% or 0.05 it is obtained that the F count  value is  24.003 and F table  is 3.554. Because the value F count > F table  then H 0 is rejected. The conclusion of this research is there are three perceptions factors that influence the healthy behaviour of employees in the work environment., namely healthy eating patterns, antismoking, and physical fitness. In addition, it was also found that there was a significant impact on the perception of NNB employees on Germas towards healthy living behaviour. Keyword : perception, behaviour, Germas, healthy life